Landslide susceptibility mapping of Al Taif urban area, Saudi Arabia, using remote sensing data and microtremor measurements: integrated approach - Abdelrahman, Kamal; Al-Amri, Abdullah M.; Al-Kahtany, Khaled; Al-Otaibi, Naif (Frontiers in Earth Science, 2023)
Many people are killed by landslides due to earthquakes or severe rain, and structures and facilities built on or near slopes sustain significant damage. Such landslides on naturally occurring slopes can be large enough to utterly destroy towns or communities. Based on remote sensing and microtremor data, the area around Al Taif has been evaluated for its susceptibility to landslides. Digital elevation model (DEM), slope angle, and slope aspect thematic layers were used to depict remote sensing data. The landslide susceptibility was extracted from remote sensing thematic data. The elevations of the Al Taif area, which range from 832 to 2594 m amsl, were identified based on the DEM. Al Taif's slope angles range from 0 o to 67.3 o degrees. Nearly flat (0 o to 4.75 o ), moderate (4.75 o to 11.1 o ), steep (11.2 o to 29.1 o ), and very steep slope ( 29.1 o ) are the different classifications for the slope.Additionally, measurements of the microtremor have been taken at 42 locations throughout the region. The horizontal-to-vertical spectral ratio (HVSR) approach was used to process and analyze microtremor data in order to determine the resonance frequency and H/V amplification factor. The findings show that, while the amplification factor varies from 1.17 to 9.28, the dominant frequency values fall between 0.3 and 12.75 Hz. To determine the frequency, amplitude, and azimuthal site response, 11 sites were eventually chosen.Furthermore, the direction of the site response in the sliding areas was parallel to the landslide directional response, indicating that the site response direction tracked the landslide direction. Practical approval of the study's findings has been given at a number of locations by field measurements at some of the Taif urban area's most recent landslide occurrence areas. These findings show that the integration between remote sensing and microtremor measurements is a useful tool for pinpointing landslide-prone areas, which helps to lessen the danger to people's lives and property. This susceptibility zonation applied to the Al Taif area has produced a good match between the distribution of the reported landslides and the zones of high susceptibility. T